Characterization of kidney stone by thermal analysis - Branco, C. H.D.; Silva, A. L. [UNESP]; Luiz, J. M. [UNESP]; Mercuri, L. P.; Matos, J. R. (Ecletica Quimica, 2009)
Ten samples of kidney stone had been studied through elemental analysis of CHN (EA), Infrared Absorption Spectroscopy and X-Ray Powder Diffraction (XRD). The thermal behavior of the samples is studied by Thermogravimetry/Derivative Thermogravimetry (TG/DTG) and Differential Scanning Calorimetry (DSC). The results of AE, IV absorption Spectroscopy and XRD showed the presence of struvite (NH4Mg [PO4].6H2O), apatite, monohydrated calcium oxalate and dihydrated calcium oxalate. The TG and DSC curves allowed to classify the samples in two different groups: Group I show typical thermal behavior of struvite and Group II present a profile thermal analytical characteristic of a mixture of calcium oxalate.
Caracterização de cálculos renais por análise térmica
Keywords: Kidney stone; Struvite; Thermal Analysis; Urinary Calculi